2015
DOI: 10.1590/s1984-82502015000200007
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic-pharmacodynamic correlation of imipenem in pediatric burn patients using a bioanalytical liquid chromatographic method

Abstract: A bioanalytical method was developed and applied to quantify the free imipenem concentrations for pharmacokinetics and PK/PD correlation studies of the dose adjustments required to maintain antimicrobial effectiveness in pediatric burn patients. A reverse-phase Supelcosil LC18 column (250 x 4.6 mm 5 micra), binary mobile phase consisting of 0.01 M, pH 7.0 phosphate buffer and acetonitrile (99:1, v/v), flow rate of 0.8 mL/min, was applied. The method showed good absolute recovery (above 90%), good linearity (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…These pharmacokinetic variabilities may be associated with differences in age, physiological characteristics such as volume of distribution, biological half-life, renal clerance and clinical condition. 1,[4][5] To Santos et al, (2011) 5 in their study evaluating only one burned child, observed differences in pharmacokinetic parameters at two different moments of evaluation, indicating that these alterations in the parameters are related to clinical status, changes in the degree of hydration, serum protein concentrations, creatinine clearance, presence of lesions, mechanical ventilation and the use of vasoactive drugs. As in the study of Kongthavonsakul et al (2016) 4 the interindividual variability in relation to pharmacokinetic parameters did not occur due to age, but due to the physiological changes of the severe clinical picture, since many of these children had some organic dysfunction, indicating the need for therapeutic monitoring and dose individualization in populations pediatric patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These pharmacokinetic variabilities may be associated with differences in age, physiological characteristics such as volume of distribution, biological half-life, renal clerance and clinical condition. 1,[4][5] To Santos et al, (2011) 5 in their study evaluating only one burned child, observed differences in pharmacokinetic parameters at two different moments of evaluation, indicating that these alterations in the parameters are related to clinical status, changes in the degree of hydration, serum protein concentrations, creatinine clearance, presence of lesions, mechanical ventilation and the use of vasoactive drugs. As in the study of Kongthavonsakul et al (2016) 4 the interindividual variability in relation to pharmacokinetic parameters did not occur due to age, but due to the physiological changes of the severe clinical picture, since many of these children had some organic dysfunction, indicating the need for therapeutic monitoring and dose individualization in populations pediatric patients.…”
Section: Resultsmentioning
confidence: 99%
“…Volume of distribution (eq.4). Vd=dose*(e -KT)/vale*(1-e -KT) [4] Antimicrobial clerance (eq.5) CL=Vd*Kel [5] The dose adjustment estimate for meropenem was performed using the equation suggested by Winter (2004)10 eq.6, maintaining an interval of 8 hours between doses, considering CIM of 1μg/mL and 4μg/mL, in 40 and 100% fT>CIM.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Formulas utilized for the calculation of Vancomycin pharmacokinetic[18][19][20].Pharmacokinetic Formula Distribution Volume (L) VD = Vancomycin dose (mg)/concentration of vancomycin (mg/L) Dialytic Clearence of vancomycin (L/h) Cl vanco = (Initial-final concentration)/Initial concentration × QD/t Half-life time T 1 2 life = 0.693 × VD/Cl % reduction in vancomycin % red = (C pre HD-C final HD)/C pre HD) × 100 VD: Distribution volume. Cl vanco: Dialytic Clearence of vancomycin.…”
mentioning
confidence: 99%